Editorial: Novel Therapeutic Approaches for HCV Chronic Infections [Hot Topic: HCV Drug Discovery and Development and Clinical Issues Related to Co-Infection with HIV (Guest Editors: Raffaele De Francesco and Giovanni Migliaccio)] - Francesco, Raffaele D.; Migliaccio, Giovanni (Infectious Disorders - Drug Targets, 2006)
Infection with hepatitis C virus (HCV) affects 170 million people worldwide. Most infections become chronic and slowly evolve to cirrhosis, liver failure, and hepatocellular carcinoma in a considerable fraction of patients. Due the chronic nature of the infection, its high prevalence, and the significant morbidity of the resulting disease, HCV will continue to represent a serious global health threat for many years to come. Our current therapeutic approaches, based on the use of interferon-a and the broad spectrum antiviral agent ribavirin, are effective in only approximately 50% of the treated patients, are associated with severe side-effects and are not suited for all patient groups. Thus, a pressing medical need dictates that we discover and develop new anti-HCV agents that are at the same time more efficacious and better tolerated by patients. After more than 15 years since the molecular identification of HCV, a number of novel agents have been identified that demonstrate anti-HCV activity in preclinical models and some of them have progressed to clinical trials. Aside from the continued improvements to interferon and ribavirin regimens, drugs that target specific steps of the HCV life-cycle are the most promising new agents. For many years, the lack of adequate laboratory animal models and the inability to efficiently propagate the virus in cultured cells have been major obstacles in identifying and evaluating all possible HCV drug targets. Therefore, efforts to develop new therapeutic agents have mostly focused on the development of drugs that inhibit the steps of HCV replication that could be readily studied in the laboratory. Thus, a number of small molecule agents have been developed that target crucial viral enzymes. The HCV NS3-4A protease and the NS5B RNA-dependent RNA polymerase play an essential role in viral replication. Following the successful paradigm established for HIV protease and reverse transcriptase, these enzymes have become preferred targets for the development of small molecule inhibitors. By combining the power of high-throughput screening with rational, knowledge-based drug design, competitive inhibitors of the NS3-4A protease as well as nucleoside and non-nucleoside inhibitors of the NS5B polymerase are being developed. Importantly, inhibitors representative of each of these classes have now demonstrated antiviral activity in early clinical trials. In addition to targeting the crucial viral enzymes, conserved sequences of the viral RNA genome are being targeted with nucleic-acid based drugs such ribozymes, antisense oligonucleotides and, more recently, small-interfering RNA (siRNA). Lin, Kwong and Perni (Discovery and Development of VX-950, a Novel, Covalent, and Reversible Inhibitor of Hepatitis C Virus NS3-4A Serine Protease) review the progress in the development of VX-950, a peptidomimetic inhibitor of the NS3-4 protease that is stabilized into the enzyme's active site by the ability to form a covalent, reversible bond with the catalytic serine residue owing to the inclusion an α-ketoamide moiety. VX-950 displays very potent anti-HCV activity when administered orally in patients, and is now rapidly progressing through clinical trials. Carroll and Olsen (Nucleoside Analog Inhibitors of Hepatitis C Virus Replication) provide a knowledgeable insight into the arena of anti-HCV nucleoside analogs. Ribonucleoside analogs incorporating 2'-C-methyl modification are selectively incorporated by the viral enzyme into the viral genome, therefore acting as potent inhibitors of HCV replication. A special difficulty in developing these agents is due to the fact that nucleoside analogs need to be converted to their respective nucleotide by the host cell metabolic machinery in order to exert their antiviral activity as